Loss of FUBP1 expression in gliomas predicts FUBP1 mutation and is associated with oligodendroglial differentiation, IDH1 mutation and 1p/19q loss of heterozygosity - Baumgarten, P.; Harter, P. N.; Toenjes, M.; Capper, David; Blank, A. -E.; Sahm, F.; Von Deimling, Andreas; Kolluru, V.; Schwamb, B.; Rabenhorst, U.; Starzetz, T.; Koegel, D.; et al. (Neuropathology and Applied Neurobiology, 2014)
The Far Upstream Element [FUSE] Binding Protein 1 (FUBP1) regulates target genes, such as the cell cycle regulators MYC and p21. FUBP1 is up-regulated in many tumours and acts as an oncoprotein by stimulating proliferation and inhibiting apoptosis. Recently, FUBP1 mutations were identified in approximately 15% of oligodendrogliomas. To date, all reported FUBP1 mutations have been predicted to inactivate FUBP1, which suggests that in contrast to most other tumours FUBP1 may act as a tumour suppressor in oligodendrogliomas.As no data are currently available concerning FUBP1 protein levels in gliomas, we examined the FUBP1 expression profiles of human glial tumours by immunohistochemistry and immunofluorescence. We analysed FUBP1 expression related to morphological differentiation, IDH1 and FUBP1 mutation status, 1p/19q loss of heterozygosity (LOH) as well as proliferation rate.Our findings demonstrate that FUBP1 expression levels are increased in all glioma subtypes as compared with normal central nervous system (CNS) control tissue and are associated with increased proliferation. In contrast, FUBP1 immunonegativity predicted FUBP1 mutation with a sensitivity of 100% and a specificity of 90% in our cohort and was associated with oligodendroglial differentiation, IDH1 mutation and 1p/19q loss of heterozygosity (LOH). Using this approach, we detected a to-date undescribed FUBP1 mutation in an oligodendroglioma.In summary, our data indicate an association between of FUBP1 expression and proliferation in gliomas. Furthermore, our findings present FUBP1 immunohistochemical analysis as a helpful additional tool for neuropathological glioma diagnostics predicting FUBP1 mutation.
EVALuna2:6655